Resuscitation from out-of-hospital cardiac arrest: is survival dependent on who is available at the scene?. Issue 1 (1st January 1999) - Soo, L H; Gray, D; Young, T; Huff, N; Skene, A; Hampton, J R
Abstract : Objective: To determine whether survival from out-of-hospital cardiac arrest is influenced by the on-scene availability of different grades of ambulance personnel and other health professionals. Design: Population based, retrospective, observational study. Setting: County of Nottinghamshire with a population of one million. Subjects: All 2094 patients who had resuscitation attempted by Nottinghamshire Ambulance Service crew from 1991 to 1994; study of 1547 patients whose arrest were of cardiac aetiology. Main outcome measures: Survival to hospital admission and survival to hospital discharge. Results: Overall survival from out-of-hospital cardiac arrest remains poor: 221 patients (14.3%) survived to reach hospital alive and only 94 (6.1%) survived to be discharged from hospital. Multivariate logistic regression analysis showed that the chances of those resuscitated by technician crew reaching hospital alive were poor but were greater when paramedic crew were either called to assist technicians or dealt with the arrest themselves (odds ratio 6.9 (95% confidence interval 3.92 to 26.61)). Compared to technician crew, survival to hospital discharge was only significantly improved with paramedic crew (3.55 (1.62 to 7.79)) and further improved when paramedics were assisted by either a health professional (9.91 (3.12 to 26.61)) or a medical practitioner (20.88 (6.72 to 64.94)). Conclusions: Survival from out-of-hospital cardiac arrest remains poor despite attendance at the scene of the arrest by ambulance crew and other health professionals. Patients resuscitated by a paramedic from out-of-hospital cardiac arrest caused by cardiac disease were more likely to survive to hospital discharge than when resuscitation was provided by an ambulance technician. Resuscitation by a paramedic assisted by a medical practitioner offers a patient the best chances of surviving the event.